94.8k views
0 votes
Simplify

6a - (3)/(8) a + 2 + (1)/(4) - (3)/(4) a


User Jim Lahman
by
4.7k points

2 Answers

3 votes

Answer:

4 7/8 a + 2 1/4.

Explanation:

6a - 3/8 a + 2 + 1/4 - 3/4 a

Bring like terms together:

= 6a - 3/8 a - 3/4 a + 2 + 1/4

= 5 5/8 a - 3/4 a + 2 1/4

= 5 5/8 a - 6/8 a + 2 1/4

= 4 7/8 a + 2 1/4 (answer).

User Lucas Pires
by
5.4k points
3 votes

Answer:

4
(7)/(8)a + 2
(1)/(4)

Explanation:

Put the like term terms together and simplify.

6a - 3/8a + 2 + 1/4 - 3/4a

= (6a - 3/8 a - 3/4 a) + (2 + 1/4)

= (6a - 9/8 a) + 9/4

= 39/8 a + 9/4

= 4
(7)/(8)a + 2
(1)/(4)

User Mehrdadep
by
4.2k points